Dynamic Modeling, Empirical Macroeconomics, and Finance Essays in Honor of Willi Semmler - Bernard, Lucas; Nyambuu, Unurjargal; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This edited volume, with contributions by area experts, offers discussions on a range of evolving topics in economics and social development. At center are important issues central to sustainable development, economic growth, technological change, the economics of climate change, commodity markets, long wave theory, non-linear dynamic models, and boom-bust cycles. This is an excellent reference for academic and professional economists interested in emerging areas of empirical macroeconomics and finance. For policy makers and curious readers alike, it is also an outstanding introduction to the economic thinking of those who seek a holistic and all-compassing approach in economic theory and policy. Looking into new data and methodology, this book offers fresh approaches in a post-crisis environment. Set in a profound understanding of the diverse currents within the many traditions of economic thought, this book pushes the established frontiers of economic thinking. It is dedicated to a leading scholar in the areas covered in this book, Willi Semmler. .
Theory and practice in a sensible economic policy mix: a glance at Willi Semmler's contribution to the empirical macroeconomics -- Iran's Nuclear Program and the West's Response: A Game -- From the Great Divergence to the Great Convergence -- Borrowing Constraints and Monetary Policy: The Inflation Tax-Net Worth Channel -- Modeling Climate Change Effects on the Renewable and Non-Renewable Resources -- A North-South model with technological spillovers, environmental degradation and structural change -- Foreign Exchange Volatility and Its Implication for Macroeconomic Stability: An Empirical Study of Developing Economies -- Keynes' microeconomics of output and labor markets -- "Wavelet-based" early warning signals of financial stress: an application to IMF's AE-FSI -- Corporate liquidity under financial constraints and macroeconomic uncertainty -- Might Tobin be right? The impact of portfolio shifts on growth and inflation in the presence of market frictions -- Business Confidence and Macroeconomic Dynamics in a Nonlinear Two-Country Framework with Aggregate Opinion Dynamics -- Self-Falsifying Prophecies.
Keywords: Economic Growth; Differentiable dynamical systems; Engineering mathematics; Macroeconomics/Monetary Economics//Financial Economics; Econometrics; Finance, general; Dynamical Systems and Ergodic Theory; Mathematical and Computational Engineering